Sustainable Business Startup at the Tourist Destinations of Bangladesh: A Popularity Study on Cox’s Bazar Sea-Beach - Rahman, Md. Mahofuzur; Karim, Md. Rezaul; Rahman, Atikur (Asian Business Review, 2025)
This study aims to propose a tourism-based startup at Cox’s Bazar Sea Beach, where products and services will be offered to tourists, with a focus on environmental sustainability. Trash left by tourists and fishing bycatches that wash up on the shore, polluting the environment, will be recycled and used in tourism facilities. For transportation, accommodation, and recreation facilities, eco-friendly measures will be taken. Moreover, the use of e-bikes, solar panels, and biodegradable, multi-use food packaging will bring a new dimension to this model. To gauge the popularity of the proposed startup, primary data have been collected from university students who have visited Cox’s Bazar Sea Beach at least twice so far. A five-point Likert scale questionnaire was developed in Google Form format, seeking data on tourists’ curiosity about eco-friendly transportation, accommodation, recreation, and food-serving initiatives. The data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results revealed that most respondents are curious about Sustainable Business Startups at Cox’s Bazar Sea Beach, Bangladesh. The findings of this article can be helpful to investors in the tourism sector when allocating financial resources, and future researchers may gain insight into tourists’ perceptions of sustainable business practices at Cox’s Bazar Sea beach.